Patterns of associated injuries in patients with facial fractures Focus on traumatic brain and cerebrovascular injuries - Kokko, Linda-Lotta (fi=Turun yliopisto|en=University of Turku|, 2026)
The prognosis of patients with facial fractures is influenced by multiple factors that need to be recognized at an early stage. Associated injuries are common, and they may delay the management of facial fractures. Conversely, significant associated injuries may remain undetected unless systematic multidisciplinary trauma diagnostics are applied. The aim of this thesis was to investigate the prevalence and risk factors for associated injuries in patients with facial fractures, focusing particularly on traumatic brain injuries (TBI) and blunt cerebrovascular injuries (BCVI). The primary objective was to identify predictors that worsen prognosis and increase mortality. The thesis is based on four registry studies of patients treated at Helsinki University Hospital between 2013 and 2018. The first study assessed the prevalence of associated injuries and compared differences between adult and elderly patients. The second examined the incidence and risk factors of BCVI in patients with craniofacial fractures. The third focused on the occurrence and risk factors for TBI in facial fracture patients. The fourth study evaluated diagnostic delay in TBI and the risk factors contributing to such delays among facial fracture patients. Associated injuries were found to be frequent, with TBI being the most common. Cranial fractures and neck injuries were strongly associated with an increased risk of TBI. High-energy trauma significantly elevated the risk of both TBI and BCVI, yet severe associated injuries were also observed following low-energy mechanisms and minor fractures. Elderly patients had a notably higher risk of associated injuries, which were more severe and carried greater mortality. Elderly persons more often experienced diagnostic delay with regard to associated TBI. The findings of this thesis highlight the importance of developing care pathways that ensure facial fracture patients are evaluated in settings where multidisciplinary trauma diagnostics and treatment are available. Careful exclusion of associated injuries and structured follow-up routines are essential. Particular attention should be given to elderly patients, as they present with a higher prevalence of associated injuries, more severe outcomes, and greater diagnostic challenges

Liitännäisvammat kasvomurtumapotilailla – Keskiössä aivo- ja kaulasuonivammat Kasvovammapotilaiden hoidon ennuste riippuu useista tekijöistä, jotka tulee tunnistaa varhaisessa vaiheessa. Oheisvammat ovat yleisiä ja voivat viivästyttää kasvomurtuman hoitoa. Toisaalta merkittäviä vammoja voi jäädä diagnosoimatta ilman moniammatillista traumadiagnostiikkaa. Tutkimuksen tavoitteena oli selvittää kasvomurtumapotilaiden oheisvammojen esiintyvyyttä ja riskitekijöitä, erityisesti aivovammojen ja tylppien kaulasuonivammojen osalta, sekä tunnistaa ennustetta heikentäväviä ja mortaliteettia lisääviä tekijöitä. Väitöskirja koostuu neljästä rekisteritutkimuksesta, joissa tarkasteltiin vuosina 2013–2018 Helsingin yliopistollisessa keskussairaalassa hoidettuja potilaita. Ensimmäisessä osatyössä selvitettiin oheisvammojen esiintyvyyttä kasvomurtumapotilailla ja eroja aikuis- ja vanhuspotilailla. Toisessa tutkittiin tylppien kaulasuonivammojen esiintyvyyttä ja riskitekijöitä kallo- ja kasvomurtumapotilailla. Kolmannessa tarkasteltiin kasvomurtumien yhteydessä aiheutuvien aivovammojen esiintyvyyttä ja riskitekijöitä. Neljännessä analysoitiin kasvomurtumapotilaiden viivettä aivovammojen diagnostiikassa sekä viiveeseen liittyviä riskitekijöitä. Oheisvammat olivat yleisiä ja aivovammat korostuivat näiden joukossa. Kallomurtumat ja kaulan alueen vammat lisäsivät aivovamman riskiä, ja korkea-energinen vammamekanismi suurensi sekä aivo- että kaulasuonivammojen riskiä. Vakavia vammoja todettiin kuitenkin myös matalaenergisten vammamekanismien ja yksinkertaisten kasvomurtumien yhteydessä. Vanhuksilla oheisvammoja esiintyi enemmän, ne olivat vakavampia ja niihin liittyi korkeampi kuolleisuus sekä suurempi riski oheisaivovamman diagnostiikkaviiveelle. Tulokset tukevat hoitopolkujen kehittämistä siten, että kasvomurtumapotilaat tutkitaan moniammatillisessa traumayksikössä, jossa oheisvammat voidaan systemaattisesti poissulkea ja seuranta varmistaa. Erityistä huomiota tulee kiinnittää vanhuksiin, joilla oheisvammojen esiintyvyys, vakavuus ja diagnostiikan haasteet korostuvat.